Impact of internal brand management on sustainable competitive advantage: An explanatory study based on the mediating roles of brand commitment and brand citizenship behavior - Qureshi, Fatima Nawaz; Bashir, Shahid; Mahmood, Asif; Ahmad, Sheraz; Attiq, Saman; Zeeshan, Muhammad (My University, 2022)
The existing literature on internal branding has often adopted a managerial-based approach and seldom considered employees’ perceptions. Therefore, there is a need to understand the perspective of frontline and non-managerial employees. In this context, the current study investigates the impact of internal brand management on brand commitment, brand citizenship behavior, and sustainable competitive advantage for the hotel industry. A survey-based quantitative data was gathered from 390 non-managerial frontline staff working in 3-, 4-, and 5-star hotels of Pakistan. The results revealed that internal brand management positively impacts brand commitment, brand citizenship behavior, and sustainable competitive advantage. Besides, brand commitment has a positive impact on brand citizenship behavior and sustainable competitive advantage. Moreover, brand citizenship behavior has a positive impact on sustainable competitive advantage. In addition, the mediating roles of brand commitment and brand citizenship behavior exist between internal brand management and sustainable competitive advantage. The research implications, together with research limitations, have also been discussed.